ANALISIS ZAT GIZI DAN DAYA TERIMA MIE KERING PENAMBAHAN TEPUNG IKAN PATIN DAN BAYAM HIJAU SEBAGAI ALTERNATIF MAKANAN BERGIZI BAGI REMAJA PUTRI - Sri Suciati; Suaebah; Yanuarti Petrika (Media Gizi Khatulistiwa, 2025)
Background: All groups, including teenagers, find noodles to be the most popular food due to  their practicality, ease of serving, deliciousness, variety of flavor options, and affordability. Despite the variety of flavors available in noodles, the sodium, sugar, and protein content in each package is nearly identical. Overconsumption of instant noodles can lead to health risks due to their preservatives and low nutritional value. Objective: The research objective is to determine the acceptability and nutrient content of dry noodles that have been enriched with catfish flour and green spinach, as an alternative nutritious food for young women. Method: This study used an experimental research design consisting of three treatments, namely: F1 (10: 35), F2 (15: 30), and F3 (20: 25). There were 25 panelists in this study. The study conducted two stages of tests: organoleptic tests to gauge the panelists' preferences for the color,  aroma, taste, and texture of dry noodles, and proximate tests and iron tests to assess the nutritional content. Results: The study found that the most preferred dry noodles in terms of color, aroma, taste, and texture were in treatment F2 (15: 30). Dry noodles in the best treatment had protein content (18.89%), fat content (1.17%), carbohydrates (61.39%), iron content (5.57%), water content (12.43%), and ash content (2.48%). Conclusion: There is an effect of color on the acceptability of dry noodles with the addition of patin fish flour and green spinach. There is an effect of color, aroma, taste, and texture on the acceptability of dry noodles fortified with patin fish flour and green spinach.